2008
DOI: 10.1111/j.1365-2672.2008.03745.x
|View full text |Cite
|
Sign up to set email alerts
|

Resistance ofEscherichia coligrown at different temperatures to various environmental stresses

Abstract: Aims: To study the influence of growth temperature on the resistance of Escherichia coli to three agents of different nature: heat, pulsed electric field (PEF) and hydrogen peroxide. Methods and Results: Escherichia coli cells were grown to stationary phase at 10°C, 20°C, 30°C, 37°C and 42°C. Survival curves to a heat treatment at 57AE5°C, to a PEF treatment at 22 kV cm )1 and to 40 mmol l )1 hydrogen peroxide were obtained and fitted to a model based on the Weibull distribution to describe and compare the ina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 25 publications
1
21
1
Order By: Relevance
“…Several model system and food studies have demonstrated increased thermotolerance of L. monocyto genes, E. coli 0157:H7, and Salmonella spp. initially exposed to sublethal temperatures between 40 and 52°C (4,10,16,27,40). Singh et al (41) reported that thermal resistance of L. monocytogenes, E. coli 0157:H7, and Salmonella spp.…”
Section: Discussionmentioning
confidence: 99%
“…Several model system and food studies have demonstrated increased thermotolerance of L. monocyto genes, E. coli 0157:H7, and Salmonella spp. initially exposed to sublethal temperatures between 40 and 52°C (4,10,16,27,40). Singh et al (41) reported that thermal resistance of L. monocytogenes, E. coli 0157:H7, and Salmonella spp.…”
Section: Discussionmentioning
confidence: 99%
“…These results agree with those previously described for Y. enterocolitica . By contrast, some authors have reported that cells grown at temperatures below the optimum are more sensitive to PEF (Álvarez, Pagán, Raso, & Condón, 2002;Russell, Colley, Simpson, Trivett, & Evans, 2000) or even that cells are more resistant at lower temperatures (Cebrián, Sagarzazu, Pagán, Condón, & Mañas, 2008).…”
Section: Pef Resistance Of E Sakazakii Grown In Different Conditionsmentioning
confidence: 95%
“…The presence of a shoulder is assumed to indicate that some threshold must be exceeded before cells are affected by the stress, that is more often observed upon exposure to mild stress, whereas the presence of a tail is assumed to indicate that a minority of the population is more resistant to the stress than the majority of population (Metselaar, 2016). Several empirical models have been proposed to describe microbial inactivation curves using high intensity PEF, such as the Hülsheger-model (Hülsheger, Potel & Niemann, 1981), sigmoidal inactivation curves based on the Fermi equation (Peleg, 1995) or log-logistic model , but the Weibull model is most frequently used (Cebrián et al, 2008;Gómez et al, 2005a;Huang et al, 2014;Rodrigo et al, 2001), probably due to its simplicity and flexibility. Enzyme inactivation is modelled using the same models as used for microbial inactivation, including first-order inactivation, Hülshegers model, Fermi's model, Weibull model and second order polynomial equations (Giner et al, 2000;Giner et al 2005;Zhong et al, 2007).…”
Section: Predictive Modelling Of Inactivation Kineticsmentioning
confidence: 99%
“…When the growth temperature is sub-optimal, micro-organisms become more sensitive to the high intensity PEF treatment (Álvarez et al, 2002;Cebrián et al 2008;Cebrián, Condón & Mañas, 2016;Ohshima, Okuyama & Sato, 2002), although differences were never larger than 1 log 10 cycle when compared to optimal growth conditions. It has 1 been proposed that variations in lipid composition of the cell membrane might be induced by growth temperature modifications, resulting in a varying PEF sensitivity (Álvarez et al, 2006;Cebrián et al, 2008;Russell, 2002).…”
mentioning
confidence: 98%
See 1 more Smart Citation